Accent dynamics in the Malaysian workplace: perceptions and implications - Nur Liyana Ashikin Abu Bakar,; Fuzirah Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Achieving a native-like accent seems to be the dream of many language learners of English due to the association of correctness with being the standard variety. Although there is a plethora of accent studies in Malaysia, the perceptions of the varieties of English accents used in Malaysia from the perspectives of organisational members remain overlooked. The present study is concerned with the expectation of English accents projected towards the corporate workers themselves and others in a workplace context. This mixed-method study aimed to explore the awareness and perception of 15 organisational members, consisting of five higher management and 10 general employees towards the British accent, American accent and Malaysian accent along with its effect on effective workplace communication. Based on the interviews and questionnaires conducted with the addition of accented audio recordings, findings revealed that respondents showcased a mismatch of perceptions. While the general employees felt the need to alter their natural accents in a professional setting, the higher management denied the accusation of accents being used as a measurement of an individual’s competence and professionalism with exceptions to several fields of work. Hence, this highlights the inconsistency of respondents’ views towards the three prominent accents in Malaysia along with the bias towards the native accent and the suppressed prejudice towards the local accent. Overall, this finding has provided a direction for educational authorities, local organisations, educators and English-learning individuals to embrace the varieties of English accents while emphasising the importance of language diversity in a workplace and academic setting.